Measurement of elements by portable x-ray fluorescence spectrometry for the study of adsorption processes: the case of Pb 2+ adsorption on soybean straw biochar - Wannaz, Eduardo Daniel (2024)
This study evaluated the reliability of portable X-ray fluorescence (pXRF) in Pb2+ adsorption kinetics and isotherm experiments using soybean straw biochar. The research aimed to compare pXRF results with those obtained through traditional atomic absorption spectrometry (AAS). Soybean straw biochar, produced at 400 ºC, was employed as the adsorbent for Pb2+. The efficiency of adsorption was assessed using Langmuir and Freundlich models. The kinetics of Pb2+ adsorption was analysed through pseudo-first-order and pseudo-second-order models. The pseudo-second-order model described the kinetics of Pb2+ adsorption on biochar better than the pseudo-first order model. Importantly, the pXRF technique demonstrated comparable results to those of AAS, making it a reliable and resource-efficient method for studying Pb2+ kinetics. The results of the isotherm analyses fit the Langmuir model, indicating a desirable and irreversible adsorption of Pb2+ on biochar. PXRF measurements on biochar allowed simultaneous observations of Pb2+ adsorption and K+ and Ca2+ desorption, highlighting ionic exchange as the primary adsorption mechanism. In conclusion, our results showcased the applicability of pXRF for Pb+2 adsorption studies in biochars, offering a valuable alternative to traditional methods. The findings contribute to the understanding of biochar as an effective adsorbent for heavy metals, emphasizing the potential of pXRF for cost-effective and efficient environmental research. In this study, we present a novel and detailed procedure that will allow other researchers to continue their studies on Pb2+ adsorption on biochar or similar matrices, significantly reducing the resources and time used and enabling the simultaneous study of the behavior of other ions participating in the process.